Ten Years of PAM: Cases, Laboratory Protocols and Therapeutic Approaches - Milanez, Giovanni De Jesus (Asian Journal of Biological and Life Sciences, 2019)
Primary Amoebic Meningoencephalitis (PAM) is considered as one of the health challenges in the medical field due to its fatal outcome to the host. This condition is caused by infection of the protozoanNaegeleria fowleri. Since the time of its description in 1965 by Fowler and Carter, there are only approximately 250 cases reported worldwide and almost 90% of these cases have a fatal outcome. Its rare occurrence and difficulty in diagnosing makes it a considerable public health concern. This review aims to at least provide an update on the current cases, strategies and therapeutic approaches in the treatment and management of PAM in the health care setting in the last ten years (2008 -2018). Due to the rare occurrence of the condition, a total of only 45 related articles using the PubMed database were included in this review. Key words used to come up with this review included “Naegleria”, “therapeutic approach”, “Primary Amoebic Meningoencephalitis” and “cases”. Studies which include the isolation ofNaegleriaspp from environment sources as well as non-human occurrences were excluded from this review. From the investigated studies from the source database, 1 out of 12 or 8.3% of PAM cases had a positive outcome where the patient had complete recovery from the condition. Although majority of cases underwent almost the same combination therapeutic regimen which includes amphotericin B and rifampicin, it seems that the key to complete recovery from this condition is the efficiency of the diagnostic procedure given to the patient by clinicians.
Keywords: Amphoteric B; Free living amoebae; Naegleria sp.; PAM; PCR